Hybrid Projective Synchronization in Mixed Fractional-order Complex Networks with Different Structure - Yang, Li-xin; Jiang, Jun; Liu, Xiao-jun (Discontinuity, Nonlinearity, and Complexity, 2026)
In this paper, a fractional-order drive-response complex network model with different order nodes is proposed for the first time. To achieve the hybrid projective synchronization (HPS) of drive-response complex network with different orders, a general strategy is proposed and effective controllers for hybrid projective synchronization are designed. The fractional operators are introduced into the controller to transform problem into synchronization problem between drive-response complex network with identical orders. Numerical simulation results which are carried show that the method is easy to implement and reliable for synchronizing the driveresponse fractional-order complex networks.